(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article defines the concept of “natural monopoly”. The role and significance for the economy of the Russian and foreign countries is described. An analysis of Russian and foreign experience in the practice of regulating natural monopolies is also carried out.